TEACHER STRATEGIES IN FORMING EARLY CHILDHOOD MORALS THROUGH HABITS AT UMINDA ISLAMIC KINDERGARTEN IN MAKASSAR CITY - Latief, Fadhilah; Musfirah; Fahrani, Nurul; Tahirah, Ilmi (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2023)
This is a qualitative descriptive study that aims to describe teacher strategies in shaping the morals of early childhood through habituation at Uminda Islamic Kindergarten in Makassar City. The research methodology used a qualitative approach with data collection techniques such as observation, interviews, and documentation. The study was conducted in the even semester of the 2022–2023 academic year. The research subjects included class teachers, students aged 5–6 years, and parents as supporting informants. The results show that teacher strategies in shaping children's morals are carried out through habituation through routine activities, role models, programmed activities, providing advice, and the application of educational rewards and punishments. These habits are reflected in children's behavior such as greeting, praying, performing religious duties, being honest, polite, helping others, being responsible, and maintaining personal and environmental hygiene. In general, children's moral development is in the Developing According to Expectations (BSH) category, although ongoing guidance and reinforcement are still needed.